The Effect of Political Connections on Earnings Quality with the Moderating Role of Family Ownership: A Study of Manufacturing Firms in Indonesia - Adinata, Kamil; Suranta, Eddy (Ilomata International Journal of Tax and Accounting, 2025)
This study aims to examine the effect of political links on the quality of earnings in manufacturing companies listed on the Indonesia Stock Exchange (IDX) between 2020 and 2022, utilizing family ownership as a moderating variable. Discretionary accruals based on the Modified Jones Model are used to quantify earnings quality using panel data regression analysis and a quantitative explanatory approach. The findings indicate that neither political connections nor family ownership have a direct effect on earnings quality. However, the quality of earnings is significantly impacted negatively by the combination of family ownership and political connections. This suggests that family ownership amplifies the negative impact of political connections on earnings quality, contrary to the initial assumption that family ownership would enhance internal control. These results support the agency theory perspective, whereby dominant family control combined with political connections exacerbates agency problems and reduces the reliability of financial reporting. This study contributes to the body of information on corporate governance in developing countries and provides stakeholders and regulators with useful advice on how to improve monitoring of companies with significant family ownership and political connections.